The Practice of Islamic Traditions among the Bugis in Bali - Mustolehudin, Mustolehudin; Noviani, Nur Laili; Muawanah, Siti; Haryanto, Joko; Zakiyah, Zakiyah; Muzayanah, Umi (Journal of Al-Tamaddun, 2024)
This study aims to explore the practice of the grave pilgrimage tradition in the Suwung Village, Denpasar, using qualitative methods. Interviews, observations, and document studies were conducted to gather data directly from the Bugis community during the grave pilgrimage. The results of the study show that the majority Hindu Balinese community can accept the Bugis migrants, who are Muslims, to express Islamic traditions in Bali. This expression of Islamic religious tradition is marked by the existence of ancient Islamic manuscripts in Muslim villages, one of which is the Bugis Suwung Village in Denpasar. Specifically, the traditions that are unique in this village are the tradition of Ngeruwah (praying for the spirits of ancestors before the arrival of the month of Ramadan), the tradition of Pagelicing Qur’an (parading the Qur’an), and the tradition of grave pilgrimage. However, the tradition of parading the Qur’an has not been practised since the 1970s. This was done because the tradition was feared to be cultised by the Muslim community in the region.